Stability of Lactobacillus acidophilus and Lactobacillus rhamnosus in minimally processed cabbage. (1st January 2013) - da Silva, Franklin Júnior Moreira; Fernandes, Cínthia Marotta; de Lima, Diana Clara Nunes; Madeira, Rodrigo Oliveira; Martins, Eliane M. Furtado; Martins, Maurilio Lopes; Lamas, Joaquim Mário Neiva; Ramos, Afonso Mota
The aim of this study was to evaluate the stability of Lactobacillus acidophilus and Lactobacillus rhamnosus in minimally processed cabbage as well as physical-chemical and microbiological characteristics of this product. After minimal process, the cabbage was soaked in solution with probiotic cultures of L. acidophilus and L. rhamnosus, which resulted in three treatments, one added with L. acidophilus, another added with L. rhamnosus, and the control treatment, without addition of probiotic. Samples were stored at 8°C for 96 hours. Analyses for acidity, pH, colour, coliforms at 45°C, Salmonella sp. and probiotic microorganisms were all carried out. Differences on pH, acidity and colour during storage period were not detected. Results of microbiological analyses showed that the samples were within standards set by Brazilian laws for Salmonella sp. and coliforms at 45°C. The probiotic microorganisms were viable in the product with counts at approximately 10 7 CFU.g –1, which shows that minimally processed cabbage can be a vehicle for these microorganisms.